PELAYANAN PASTORAL KONSELING OLEH PELAYAN KHUSUS KEPADA ISTRI YANG TELAH BERCERAI - Opit, Preysilia Kirey Eleison; Wagiu, Meily M.; Brek, Yohan (PT. Giat Konseling Nusantara, 2024)
Divorce is something that is contrary to the teachings of the Bible, but in almost every church there are cases of divorce that occur. Divorce creates problems in the life of the congregation and if not handled well it will have negative impacts. The church needs to highlight the problem of divorce and find solutions to address existing problems, for example by providing pastoral counseling services to congregation members who have divorced. Women are still often considered as weak figures and are often victims in the household, there are many women who receive inappropriate treatment and become victims of violence. Pastoral counseling services can be used as a tool that can help churches provide assistance to congregations who are in trouble.